Fermi-LAT follow-up observations in seven years of real-time high-energy neutrino alerts - Garrappa, S.; Buson, S.; Sinapius, J.; Franckowiak, A.; Liodakis, I.; Bartolini, C.; Giroletti, M.; Nanci, C.; Principe, G.; Venters, T. M. (EDP Sciences, 2025)
The realtime program for high-energy neutrino track events detected by the IceCube South Pole Neutrino Observatory releases alerts to the astronomical community with the goal of identifying electromagnetic counterparts to astrophysical neutrinos. Gamma-ray observations from the Fermi-Large Area Telescope (LAT) enabled the identification of the flaring gamma-ray blazar TXS 0506+056 as a likely counterpart to the neutrino event IC-170922A. By continuously monitoring the gamma-ray sky, Fermi-LAT plays a key role in the identification of candidate counterparts to realtime neutrino alerts. In this paper, we present the Fermi-LAT strategy for following up high-energy neutrino alerts applied to seven years of IceCube data. Right after receiving an alert, a search is performed in order to identify gamma-ray activity from known and newly detected sources that are positionally consistent with the neutrino localization. In this work, we study the population of blazars found in coincidence with high-energy neutrinos and compare them to the full population of gamma-ray blazars detected by Fermi-LAT. We also evaluate the relationship between the neutrino and gamma-ray luminosities, finding different trends between the two blazar classes BL Lacs and flat-spectrum radio quasars.